Pemberdayaan Guru IPA melalui Pelatihan Pembuatan Media Pembelajaran Augmented Reality (AR): Empowering Science Teachers through Augmented Reality (AR) Learning Media Creation Training - gani, Abdul Gani; Nasrullah; Irwan Yon Hadi; Sukranudin (Indonesia, 2024)
This study explores the empowerment of science teachers through training in the development of Augmented Reality (AR)-based learning media, recognizing the increasing demand for innovative digital tools to improve teaching quality in science education. The objective was to enhance teachers’ technological literacy, pedagogical skills, and motivation to integrate AR into classroom practice. A quasi-experimental design was employed, combining quantitative and qualitative approaches. Data collection consisted of pre-test and post-test assessments to measure knowledge improvement, classroom observations to evaluate teacher engagement, and interviews to capture perceptions and experiences. Quantitative analysis indicated a substantial increase in teachers’ understanding and practical competence in designing AR learning materials. Participants successfully produced high-quality AR media aligned with curriculum objectives, demonstrating improved creativity and technological confidence. Qualitative findings supported these results, showing that teachers perceived AR as an effective tool for simplifying abstract science concepts, fostering student engagement, and encouraging active learning. Moreover, the training provided opportunities for collaborative professional development, creating a supportive environment for innovation. The study contributes to the growing body of literature on digital-based teacher development by providing empirical evidence of AR’s potential to transform instructional practices. It also suggests that future research should focus on long-term implementation, sustainable training models, and the impact of AR adoption on student learning outcomes.